PENGARUH KOMPETENSI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Pristiningsih, Siska (Universitas Slamet Riyadi, 2015)
Purpose of this research to analyze the effect of competention, leadership and motivation on employee performance dan to analyze effect of competention and leadership on employee performance with motivation are moderation. Design research is survey on employees of CV. Harapan Baru Surakarta. Population are 56 employees with sampling technique used sensus. The type of data used quantitative and qualitative data. Source of data used primary data and secondary data. The technique of collecting data used questionnaires and literature. The data analysis technique used regression with moderation. The results showed that competention has significant effect on employee performance. Leadership has significant effect on employees performance. Motivation has significant effect on employees performance. Motivation did not moderate effect of competention on employees performance. Motivation did not moderate effect of leadership on employees performance. Keywords: competention, leadership, motivation and performance